Cashless Payment System In Rural Areas Using Mobile Banking Application - Dr. V. Josephine Lourdes De Rose, Ms. S.J.Sureya (Drugs and Cell Therapies in Hematology, 2021)
A Cashless payment system helps the economy to transform into cashless economy in which all types of transactions are accepted through digital means. It includes debit card, credit card, electronic banking, point of sales and digital wallets. This system has highly accepted during demonetisation period and even made the rural people to use mobile banking application for cashless payment system. The study focused on the perception of rural consumer using mobile banking application. The researcher used descriptive research design with well structured questionnaire to collect primary data from the respondents. The study found that perception of different age group influences the purpose of using the application, preference of choosing a particular app and satisfaction level of the consumer. Hence further study should focus on the factors influencing the rural people to use these services.